DNA: Diplomacy, Negotiations, and the Arctic: An analysis of the friendliest land border dispute in the world, the Hans Island conflict - Gabriele Satrauskaite 1995- (2023)
This master’s thesis aims to analyze the Hans Island conflict through the lens of constructivist theory in international relations with the help of a case study as a method. The thesis explores the reasons why this conflict took over 50 years to be settled, how it was solved, and what was the outcome. The first part of the thesis includes a general introduction to the topic as well as introductions to negotiations, conflicts, and the Arctic region. The timeline of the events during the conflict as well as the analysis of the matter is followed up in the second part of the thesis. The thesis concludes with the findings chapter, where the reader is presented with answers to the research questions. The main conclusion of the theory is that the Hans Island conflict is a very rare example of how land border conflicts are solved. There was no threat throughout the conflict, no military presence. The three states, Canada, Denmark, and Greenland have shown a willingness to work together in a peaceful manner to solve the issues. The reasoning for a peaceful dispute could be the fact that the three states are allies within the larger organization, which means that the three states have similar views and beliefs in the international environment. The Agreement was officially signed on the 14th of July 2022, which marked a very significant moment for Indigenous communities. Throughout the process of solving the conflict, Indigenous communities were consulted and involved. This is seen as a first step in the actual recognition of Indigenous territories. This thesis explores the conflict using the collection of available data from all three states and analyzing the deeper meaning of the state's views on the conflict resolution process.